An Efficient Constant Train Regulation Method Based on Train Group Distribution - LI Denggen; LIANG Ye; XIAO Xiyu; LI Juanjuan (Kongzhi Yu Xinxi Jishu)
In the event of an emergency in urban rail transit, train will not be able to run according to the existing operating chart, and the adjustment of the train at equal intervals can simply and effectively restore the operational order. Aiming at the problem of train running disorder, in order to optimize the efficiency of restoring operation order, a constant train regulation method is designed in this paper. By calculating the tracking interval between each train, a relative position in the time dimension of the train group is obtained; taking the shortest time of the train group to constant interval status as the optimization goal, the optimal time to be adjusted for each train is obtained. Finally, by adjusting the stopping time and the operation level, the time to be adjusted of each train is adjusted to zero, so that the train group can travel at equal intervals. In this paper, five scenarios are designed for simulation verification, and the method is compared with the average interval method and the arrival time judgment method. The results show that the adjustment effect of this method is better than the other two ones', which verifies the engineering application effectiveness of this method and the efficiency of the adjustment process.